2019
DOI: 10.5194/aab-62-297-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a low-energy and enzyme-supplemented diet on broiler chicken growth, carcass traits and meat quality

Abstract: Abstract. The objective of this study was to evaluate the impact of a low metabolizable energy (low-ME) diet supplemented with a multienzyme blend (KEMZYME®) on the growth performance, carcass traits and meat quality of chickens. A total of 108 broiler chicks (Ross 308) were randomly allocated to three experimental groups with six replicates per treatment and five birds per replicate; the groups were treated as follows: a control diet with no additive and standard metabolizable energy (ME; 3200 kcal kg−1); a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
7
15
1
Order By: Relevance
“…The results of the carcass organs were in agreement with the other researchers' results (Liu et al, 2007;Hussein et al, 2019Hussein et al, , 2020. Farran et al (2010) reported that the muscle weights were not affected by the inclusion of enzyme preparations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the carcass organs were in agreement with the other researchers' results (Liu et al, 2007;Hussein et al, 2019Hussein et al, , 2020. Farran et al (2010) reported that the muscle weights were not affected by the inclusion of enzyme preparations.…”
Section: Discussionsupporting
confidence: 91%
“…However, the combination of xylanase, amylase, and protease works better than protease supply alone (Olukosi, 2007). This method could reduce the number of raw matter ingredients needed for poultry diets such as yellow maize and soy meal, and reduce production costs (Hussein et al, 2019(Hussein et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Attia et al (16) revealed that supplementing poultry diet with multienzyme enhanced the economic cost of the diets. However, the composition and the type of enzyme mixture determine the effect of the multienzyme supplementation on poultry production performance (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Interesting finding was observed in this study, at which the relative weight of pancreas was lower in BLPR than in other broiler chickens. The reduction in size of pancreas may be associated with the reduced production of pancreatic enzymes [36], which consequently compromised nutrient digestibility of broiler chickens. This may therefore partly explain the lower feed efficiency in BLPR and TRPR birds.…”
Section: Discussionmentioning
confidence: 99%